Interacting Roles of Breeding Geography and Early-Life Settlement in Godwit Migration Timing - Battley, Phil F.; Conklin, Jesse R.; Parody-Merino, Ángela M.; Langlands, Peter A.; Southey, Ian; Burns, Thomas; Melville, David S.; Schuckard, Rob; Riegen, Adrian C.; Potter, Murray A. (Frontiers in Ecology and Evolution, 2020)
While avian migration timing is clearly influenced by both breeding and non-breeding geography, it is challenging to identify the relative and interdependent roles of endogenous programs, early-life experience, and carry-over effects in the development of adult annual schedules. Bar-tailed godwits Limosa lapponica baueri migrate northward from New Zealand towards Asian stopover sites during the boreal spring, with differences in timing between individuals known to relate to their eventual breeding-ground geography in Alaska. Here, we studied the timing of northward migration of individual godwits at three sites spanning 1,100 km of New Zealand’s 1,400-km length. A lack of morphological or genetic structure among sites indicates that the Alaskan breeding population mixes freely across all sites, and larger birds (southern breeders) tended to migrate earlier than smaller birds (northern breeders) at all sites. However, we unexpectedly found that migration timing varied between the sites, with birds from southern New Zealand departing on average 9.4–11 days earlier than birds from more northerly sites, a difference consistent across four years of monitoring. There is no obvious adaptive reason for migration timing differences of this magnitude, and it is likely that geographic variation in timing within New Zealand represents a direct response to latitudinal variation in photoperiod. Using resightings of marked birds, we show that immature godwits explore widely around New Zealand before embarking on their first northward migration at age 2–4 years. Thus, the process by which individual migration dates are established appears to involve: (1) settlement by sub-adult godwits at non-breeding sites, to which they are highly faithful as adults; (2) a consequent response to environmental cues (i.e. photoperiod) that sets the local population’s migration window; and (3) endogenous mechanisms, driven by breeding geography, that establish and maintain the well-documented consistent differences between individuals. This implies that behavioral decisions by young godwits have long-lasting impacts on adult annual-cycle schedules, but the factors guiding non-breeding settlement are currently unknown.